2013
DOI: 10.1007/s12105-013-0500-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomesenchymal Chondromyxoid Tumour of the Posterior Tongue

Abstract: Ectomesenchymal chondromyxoid tumor (ECMT) is a rare benign neoplasm arising in the tongue. With only 45 cases reported in the literature, there are several unique features defining this lesion. Firstly, almost all patients present with an asymptomatic slow growing mass on the anterior dorsum of the tongue. At the microscopic level, it is recognizable as a well-circumscribed unencapsulated proliferation of uniform round to fusiform cells embedded in a chondromyxoid matrix. Lastly, the immunohistochemistry prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 7 publications
1
25
1
2
Order By: Relevance
“…Similarly to Smith et al's original findings, the vast majority of subsequently described ECTs have been documented on the anterior tongue surface, although there are a handful of cases in which tumours have been located on the posterior aspect of the tongue [1, 5] and one case where the neoplasm grew on the hard palate of a 13-year-old boy, described by Gouvêa et al in 2012 [6]. There was another reported case of ECT on the hard palate reported in 2006; however, the diagnosis in this case has been the subject of controversy due to an apparent lack of appropriate documentation [7].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly to Smith et al's original findings, the vast majority of subsequently described ECTs have been documented on the anterior tongue surface, although there are a handful of cases in which tumours have been located on the posterior aspect of the tongue [1, 5] and one case where the neoplasm grew on the hard palate of a 13-year-old boy, described by Gouvêa et al in 2012 [6]. There was another reported case of ECT on the hard palate reported in 2006; however, the diagnosis in this case has been the subject of controversy due to an apparent lack of appropriate documentation [7].…”
Section: Discussionmentioning
confidence: 80%
“…Ectomesenchymal chondromyxoid tumours (ECTs) are rare mesenchymal soft tissue neoplasms that typically present as a slow-growing asymptomatic mass on the anterior dorsum of the tongue, or, much less frequently, on the posterior tongue [1]. Microscopically, ECTs are identified as unencapsulated, well-circumscribed proliferations of uniform round to fusiform cells embedded within chondromyxoid matrices [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECT was first described in 1995, 1 with 52 cases reported in the English-language literature: 50 cases were in the tongue; 1 was in the hard palate; and 1 was in the buccal mucosa. [1][2][3][4][5][6][7][8] The cases described in the literature reported that ECT most commonly affects adults in the third to sixth decades of life. Clinically, ECT presents as a slow-growing, painless, firm, wellcircumscribed, submucosal nodule, covered by normal mucosa, that appears to involve only the oral cavity and usually is located on the anterior dorsum of the tongue.…”
Section: Can You Make the Diagnosis?mentioning
confidence: 99%
“…The authors who first described this tumour supported an ectomesenchymal (neural crest) origin, owing to the strong and diffuse tumour cell immunoreactivity for S100 and glial fibrillary acidic protein (GFAP) . An origin from minor salivary glands appears to be less likely, because of the absence of minor salivary glands in the anterior tongue dorsum. Also, the immunophenotype of the neoplastic cells differs from that of salivary myoepithelial tumours …”
Section: Introductionmentioning
confidence: 99%